Targeting the Hepcidin-Ferroportin Axis in the Diagnosis and Treatment of Anemias - Nemeth, Elizabeta (Hindawi Publishing Corporation, 2010)
The hepatic peptide hormone hepcidin regulates dietary iron absorption, plasma iron concentrations, and tissue iron distribution. Hepcidin acts by causing the degradation of its receptor, the cellular iron exporter ferroportin. The loss of ferroportin decreases iron flow into plasma from absorptive enterocytes, from macrophages that recycle the iron of senescent erythrocytes, and from hepatocytes that store iron, thereby lowering plasma iron concentrations. Malfunctions of the hepcidin-ferroportin axis contribute to the pathogenesis of different anemias. Deficient production of hepcidin causes systemic iron overload in iron-loading anemias such as beta-thalassemia; whereas hepcidin excess contributes to the development of anemia in inflammatory disorders and chronic kidney disease, and may cause erythropoietin resistance. The diagnosis of different forms of anemia will be facilitated by improved hepcidin assays, and the treatment will be enhanced by the development of hepcidin agonists and antagonists.